Multiphase flow challenges in drilling, completions, and injection: Part 1 - C.E. Obi; A.R. Hasan; M.A. Rahman; D. Banerjee (Petroleum)
This review addresses the diverse applications of multiphase flows, focusing on drilling, completions, and injection activities in the oil and gas industry. Identifying contemporary challenges and suggesting future research directions, it comprehensively reviews evolving applications in these multidisciplinary topics. In drilling, challenges such as gas kicks, cutting transport, and hole cleaning are explored. The application of immersion cooling technology in surface facilities for gas fields utilized in integrated bitcoin mining is also discussed. Nanotechnology, particularly the use of nanoparticles and nanofluids, shows promise in mitigating particulate flow issues and controlling macroscopic fluid behavior. Nanofluids find applications in drilling for formation strengthening and mitigating formation damage in completions as highlighted in this work, as well as in subsurface injection for enhanced oil recovery (EOR), waterflooding, reservoir mapping, and sequestration tracking. The review emphasizes the need for techno-economic analyses using multiphase flow models, particularly in scenarios involving fluid injection for energy storage. Addressing these multiphase flow challenges is crucial for the future of energy diversity and transition initiatives, offering benefits such as financial stability, resilience, sustainability, and reliable supply chains. The first part of this review presents the application of multiphase (typical gas, liquid, solid) flow models and technology for drilling, completion, and injection operations. While the second part reviews the applications of multiphase particulate (nanofluid) flow technology, the use of computational fluid dynamics (CFD), machine learning (ML), and system modeling for multiphase flow models in drilling, completions, and injection operations.